In Vitro Antioxidant and Anti-Convulsant Activity of Methanolic Extract of Sarasvata churna Using scPTZ and MES Models - Kaushik, Rahul; Jain, Jainendra; Mazumder, Avijit (Natural Products Journal, The, 2021)
Background: Sarasvata churna is an Ayurvedic formulation for treatment and management of epilepsy and other maniac disorders since thousands of years. Objective: This study aimed to evaluate the in vitro antioxidant potential, total phenolics and flavonoids content, acute-oral-toxicity and anticonvulsant activity of Sarasvata churna. Materials & Methods: In vitro antioxidant activity of methanolic extract of Sarasvata churna against Nitrous oxide, Peroxide, Phosphomolybdenum and Hydroxyl radicals was performed using Colorimetry against Ascorbic acid as standard along with estimation of total phenolic and flavonoids content. Acute oral toxicity was evaluated using OECD guidelines. Extract in carboxymethyl cellulose at doses of 50,75,100,125,150 and 200 mg/kg was screened for anticonvulsant activity using subcutaneous Pentylenetetrazole and Maximal Electroshock models in Swiss Albino Mice (n=6). Sodium valproate was used as standard. Results: IC50 value of methanolic extract in the Nitrous oxide, Peroxide, and Hydroxyl free radical scavenging assay was found to be 165mg/ml, 32.5mg/ml and 253.9mg/ml respectively as compared to 61.58μg/ml, 333.44μg/ml and 351μg/ml respectively of standard Ascorbic acid. In acute oral toxicity screening, animals did not show any signs of acute and delayed toxicity even up to a dose of 2000mg/kg. Extract offered a protection of 57.39% and 85.26% in scPTZ model (P<0.0001) and 74% and 96.38% in MES model (P<0.0001) at doses of 50 and 200mg/kg respectively as compared to standard at 95% Confidence interval (ANNOVA, Tukey test) indicating a dose-dependent protection. Conclusion: Sarasvata churna’s potentials are comparable with standard antioxidant Ascorbic acid and antiepileptic drug Sodium valproate. This preclinical and toxicity screening data can be beneficial in establishing the scientific basis for the use of Sarasvata churna in management of epilepsy.
Keywords: ayurvedic